EDUCATIONAL PACKAGE FOR DETECTION AND STIMULATION OF TODDLER DEVELOPMENT - Aisyah, Risqi Dewi; Ersila, Wahyu; Faradisi, Firman (Universitas STRADA Indonesia, 2024)
Approximately 52.9 million children under 5 globally have developmental disorders. Early detection is crucial for addressing these issues. This study aimed to assess the impact of a detection and stimulation education package on parental knowledge and attitudes. Using a pseudo-experimental, cross-sectional design with cluster random sampling, 78 respondents were analyzed via T-test. Results revealed significant improvement in mothers' knowledge and attitudes following the education package (p=0.001). Providing such packages enhances awareness and understanding of toddler development. Health professionals, particularly midwives, are advised to collaborate in early detection and stimulation programs, ensuring comprehensive education for parents. This collaborative effort can significantly contribute to addressing developmental challenges in young children.